Pengembangan Sistem Informasi Penggajian Pegawai dan Dokumentasi Pekerjaan Berbasis Web (Studi Kasus: PT. Yuga Elektro Tuban) - Raga Saputra Heri Istanto; Ismiarta Aknuranda; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The lack of technology support in the yuga elektro tuban company causing inefficiency in the process of making financial reports and job documentation by administration functionaries. To improve work efficiency, technology support is required that provides the functions to support both process through an information system. This reserach was conducted to determine whether an prototype of information system capable to demonstrate the functions to support both process can be built properly. To answer those question, requirement analysis, design, and implementation of information system was done using object oriented approach. Then, the result of implementation tested to determine wheter system can work as the identified requirement analysis. The requirement analysis produces the information system requirement identification and visualization of the system capability in the form of use case diagram. The resultof design is the object interaction model documentation in the form of sequence diagram, object model in the form of class diagram, data base design, algorithm design, and user interface design. The result is an prototype of information system. Information system then was tested based on functional and nonfunctional requirement that presenting valid results on every test performed. In the end, we can draw a conclusion that information system was built properly.